Extra-EU Imports of Clothing and EU Preferential Trade Policies in the Post-Quota Era: The Position of Asian Suppliers in the Largest World Market for Clothing Imports - William E. James; Juan Paolo Hernando (Asian Development Bank (ADB), 2008)
The European Union (EU) became the largest single market for clothing imports in 2007, surpassing the United States (US). This paper examines the competitive position of suppliers from developing Asia in the expanded EU clothing market relative to other non-EU suppliers, including those receiving preferences under the complex system of EU preferential trade programs. The paper finds that competitive Asian suppliers, led by the People's Republic of China (PRC), have performed well in the EU clothing market since quotas were eliminated under the Agreement on Textiles and Clothing (ATC) in 2005. It also examines price movements in imported clothing under the ATC (2004) and after quotas were abolished (2005), and then examines how the imposition of safeguards on the PRC (2006–2007) affected prices. The relative position of various groups of suppliers in terms of unit prices is then compared with the PRC and the world as a whole. Finally, time trends in price movements are examined for the PRC and from all suppliers. The findings indicate that the end of quotas on the PRC on 1 January 2008 should bring renewed downward pressure on prices in the EU clothing market, and will require other suppliers to become more efficient, else they lose market share.
hdl:11540/2357
Keywords: 330; Bekleidung; Import; Handelspräferenzen; EU-Staaten